Organización contable en la empresa “STAR MEDIA PC” de la ciudad de Loja, período del 01 de abril al 30 de junio del 2022 - Gálvez Campoverde, Jonathan David (2023)
The degree work called ACCOUNTING ORGANIZATION IN THE COMPANY "STAR MEDIA PC" OF THE CITY OF LOJA, PERIOD FROM APRIL 01 TO JUNE 30, 2022, was developed with the purpose of making known to its owner manager the importance of the accounting organization, indicating what its economic and financial reality is, the importance of keeping an adequate control in its accounts and with the presentation of the financial statements that leads to better decision-making with efficiency and effectiveness. For the execution of the Curriculum Integration Work and fulfillment of the general objective, an accounting organization was carried out with which it contributes to the improvement of internal functioning, the manager does not have a detailed record of the sales that he makes, which originates conflicts as it is in the accounts. inventory, customers and suppliers, with the implementation of the accounting organization records of purchases and sales made with cash, banks or credit were created, with an initial inventory of $154,470.33 in merchandise, the kardex work with the weighted average method and we Provides information on existing and out of stock products. At the end of the accounting organization, the financial statements are presented where the income statement reflects a total income of $10.146.80, a total of expenses of $8.7811,92 generating a profit for the year of $1.334,88, the statement of financial position presents total assets of $186.718,25, in liabilities a total of $16.260,09 and total equity of $170.458,17, the cash flow statement shows net cash used in operating activities of $28.073,28; The implemented accounting organization has been of great help to improve business activities and provide more accurate and reliable information to the owner manager of the economic and financial situation of the company.